Development and validation of a modified TM25 journal bearing test equipment for load-carrying capacity and frictional torque measurement - Nurcahya Nugraha; Jamiatul Akmal; Martinus Martinus; Ahmad Su'udi; Rizal Nazarrudin; Eko Wahyu Saputra; Wahyu Adani; Fauzan Azima (Jurnal Polimesin, 2026)
This study developed and validated a low-cost measurement platform by upgrading an existing TM25 journal bearing demonstration unit. The original apparatus was limited to pressure distribution observation through manometer tubes, whereas the modified system integrated load cells and an Arduino-based data acquisition system to measure load-carrying capacity and frictional torque in real time. Load cell calibration was conducted using an eight-point dead-weight method with three repetitions, resulting in a calibration deviation of less than 2% across the test range. Experimental testing was performed at five rotational speeds (1000–2000 rpm) using three lubricant grades (SAE 10W-30, SAE 10W-40, and SAE 20W-50) to evaluate their influence on bearing performance. The results show that both load-carrying capacity and frictional torque increase with rotational speed and lubricant viscosity, with the highest values obtained using SAE 20W-50. The measured trends agree well with the original TM25 pressure distribution data and are consistent with hydrodynamic lubrication theory. The modified test equipment provides stable and repeatable measurements and extends the functionality of the TM25 unit as an experimental platform for tribology education and journal bearing performance analysis.